PENGARUH PERNIKAHAN DI BAWAH UMUR AKIBAT PERJODOHAN DARI ORANG TUA PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NO. 1 TAHUN 1974 - Yuliana Nurfadilah; Dzulfikar Rodafi; Humaidi Kaha (Jurnal Hikmatina, 2022)
Underage marriage is one of the social phenomena for people who are easy to be influenced by the culture of marrying or matching their children who are still small to maintain the honor of the family when he has not found his soul mate. According to Hanafiyah scholars, marriage is a contract that allows a man to have rights and use women's entire body to obtain satisfaction and enjoyment, in Law no. 1 of 1974 concerning the marriage that explained that marriage is a physical and spiritual bond between a person men and women as legal husband and wife in order to form a happy and eternal family based on God Almighty. Researcher using a qualitative approach. Strategies used in research The qualitative research discussed is a field research strategy or case study. The results of studyshow that the effect of underage marriage is due to arranged marriages These parents show positive and negative influences in the family because they can help ease the burden on the family and stay away from public gossip to maintain the good name of the family, and there are fights or incompatibility between couplesbecause they don't know each other and there are also difficulties economy in the household so that the family intervenes to help needs in his family.